2018
DOI: 10.1016/j.theriogenology.2017.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increasing equilibration time of diluted bull semen up to 72 h prior to freezing on sperm quality parameters and calving rate following artificial insemination

Abstract: An equilibration period of approximately 3-4 h prior to semen cryopreservation is standard practice for maintaining membrane integrity and motility of bull sperm. However, a number of studies indicate that an overnight equilibration period prior to freezing results in improved post-thaw semen quality thus optimising pregnancy rates. The aim of this study was to assess the effect of increasing the equilibration time of bull semen up to 72 h before freezing on sperm quality parameters and calving rate (CR) follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 39 publications
3
18
0
2
Order By: Relevance
“…The method of equilibration in the refrigerator (5 o C) was already used in previous studies (Soltan et al, 2016;Elhammali et al, 2019). The durations of equilibration were 4 and 6 hours at 4 o C, according to Fleisch et al (2017) and Murphy et al (2017), respectively. Furthermore, the equilibrated semen was transferred into a Styrofoam box containing liquid nitrogen with a depth of about 10 cm above the surface of liquid nitrogen for 10 minutes, and then the semen was ready to be frozen into liquid nitrogen at -196 o C. The post-thawing evaluation was done by placing the straw into the warm water at 37 o C for 30 seconds with an observation time of 0 hours, 0.5 hours, and 1 hour.…”
Section: Semen Processingmentioning
confidence: 99%
“…The method of equilibration in the refrigerator (5 o C) was already used in previous studies (Soltan et al, 2016;Elhammali et al, 2019). The durations of equilibration were 4 and 6 hours at 4 o C, according to Fleisch et al (2017) and Murphy et al (2017), respectively. Furthermore, the equilibrated semen was transferred into a Styrofoam box containing liquid nitrogen with a depth of about 10 cm above the surface of liquid nitrogen for 10 minutes, and then the semen was ready to be frozen into liquid nitrogen at -196 o C. The post-thawing evaluation was done by placing the straw into the warm water at 37 o C for 30 seconds with an observation time of 0 hours, 0.5 hours, and 1 hour.…”
Section: Semen Processingmentioning
confidence: 99%
“…Although the equilibrium step is considered an important period for interactions between environmental components (medium components) and sperm cells (Leite et al, 2010;Murphy et al, 2018;Watson, 1979), its length remains debatable. Leite et al (2010) and Fleisch et al (2017) reported that longer periods of equilibrium time provided greater preservation of sperm membranes.…”
Section: Discussionmentioning
confidence: 99%
“…After cooling, sperm are maintained between 6°C and 4°C for a period of time (named equilibrium phase). It is believed that the equilibrium time is important for adaptation of sperm membrane to low temperatures (Fleisch et al, 2017;Leite et al, 2010;Muiño et al, 2007), thereby allowing water translocation and reduction of injuries caused by ice nucleation (Murphy et al, 2018;Vishwanath & Shannon, 2000). During the freezing stage (below 0°C), sperm are exposed to the effects of ice crystal formation, hyperosmolarity (Hammerstedt et al, 1990), cellular dehydration (Grötter et al, 2019), and changes in cell volume and protein denaturation (Ugur et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin treatment has successfully been used to initiate ovarian cyclicity in anoestrous buffalo heifers 11 and increase plasma concentrations of GnRH and gonadotropins, promoting follicular growth and ovulation 12, 13 . The conception rate following AI is usually between 30% and 70% 14–22 . Early embryonic development may be negatively affected by insufficient progesterone (P4) production, with pregnancy failure attributed to insufficient luteal P4 production during early embryonic development 23 …”
mentioning
confidence: 99%